Edukasi Kesehatan Reproduksi Wanita pada Pengajian Aisyiyah Turisari, Desa Palur Kulon, Kecamatan Mojolaban, Kabupaten Sukoharjo - Ropitasari Ropitasari; Rachmi Fauziyah Rahayu; Retno Tri Astuti Ramadhana (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Knowledge of reproductive health is not only important for a midwife or general practitioners to have, but it is also very important for every woman as a young woman or a wife or as a mother or prospective mother of her children for the sake of health in order to achieve women's welfare. Reproductive health is a healthy condition in all organ systems, functions and reproductive processes. The aim of this service to educate on women's reproductive health is to provide knowledge in order to behave correctly and accurately regarding the reproductive health of each woman. The method of implementing this activity is through educational outreach by a team of D3 Midwifery lecturers, as paramedics and doctors as a medical team, as well and midwifery students, with written materials and applicative videos. The results of the activity were followed by 105 women who are part of the routine recitation activities of mothers, 50 women of productive age divided into 40 reproductive ages, 4 early adolescents, 6 late adolescents, and also 55 elderly women. Questionnaires were given after the activity, 60 women had good knowledge, 25 women had moderate knowledge and 15 women had poor knowledge about women's reproductive health, the rest did not fill out the questionnaire because of the 5 women over 70 years old. In conclusion, there are still some women who do not understand about maintaining their reproductive health, so this educational activity needs to be carried out periodically.